Assessment of level of depression and anxiety in pre- and postoperative stages: A prospective cross-sectional study in SCB Medical College, Cuttack - Srikanta Panda; Narendranath Samantaray; Monisha Patanaik; Debasish Sahoo; Anshuman Sarangi; Somanatha Jena (Apollo Medicine)
Objectives: Mood disorders are considered to be prevalent in hospitalized patients. Our study aimed to investigate the prevalence of depression and anxiety symptoms in pre- and postoperative stage in surgical patients. Methods: We included 60 surgical patients in this cross-sectional study which includes 43 male and 17 female patients and average age of 38.8 years. Hamilton Anxiety Rating Scale and Hamilton Depression Rating Scale were used to screen for symptoms of depression and anxiety at 12 h after admission for electively scheduled surgeries and 12–24 h after the surgery for patients undergoing emergency surgery. Results: In presurgery stage, anxiety was found to be prevalent in 43.3% of patients while depression is 38%. In postsurgery stage, anxiety and depression were found in 18.3% and 35% of patients, respectively. Conclusions: Both anxiety and depression are highly prevalent in pre- and postoperative stage of surgery. Such symptoms should be attended with more seriousness, otherwise would lead to higher morbidity and mortality.